Bridging the Gap: The Impact of Compensatory Measures on Mountain Farming in Piedmont - Francesca Moino; Alessandro Giacardi; Giovanbattista Califano; Roberto Cagliero (Bio-based and Applied Economics, 2025)
This study examines the impact of the Rural Development Program (RDP)  on reducing income disparities between farms in mountainous and non-mountainous areas in Piedmont, Italy. Using Farm Accounting Data Network data from 2012–2022, the analysis focuses on cattle, sheep and goats, and fruit farms, with 562 farms (3,557 observations; 39% in mountainous areas). A pooled multivariate regression assesses income disparities excluding RDP support, RDP’s effectiveness in mitigating gaps, and the role of compensatory allowance.